2020
DOI: 10.1108/mip-11-2019-0574
|View full text |Cite
|
Sign up to set email alerts
|

Modelling value co-creation in triadic B2B industrial relationships

Abstract: PurposeThis study examines the triadic approach of value co-creation (VcC) in B2B relationships between the industrial manufacturer, its main supplier and its main client, by validating VcC as antecedent of Trust and Commitment, which, in turn, affect Satisfaction.Design/methodology/approachA model studies the association of VcC to Trust, Commitment and Satisfaction, the latter in its economic and social dimensions. The relationships in the model are empirically contrasted twice (with suppliers and clients) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 65 publications
(108 reference statements)
2
34
0
Order By: Relevance
“…Extant literature proposes different conceptualizations of value co‐creation, which has made it challenging to achieve definitional consensus (Grönroos & Voima, 2013; Sales‐Vivó et al, 2020). For example, McColl‐Kennedy et al (2012) identified as many as 27 different definitions of the construct.…”
Section: Conceptual Development and Hypothesesmentioning
confidence: 99%
“…Extant literature proposes different conceptualizations of value co‐creation, which has made it challenging to achieve definitional consensus (Grönroos & Voima, 2013; Sales‐Vivó et al, 2020). For example, McColl‐Kennedy et al (2012) identified as many as 27 different definitions of the construct.…”
Section: Conceptual Development and Hypothesesmentioning
confidence: 99%
“…Notwithstanding, other authors have suggested a triadic approach for understanding RQ dynamics along the value chain in B2B contexts (e.g. Sales-Vivó et al , 2020; Zolkiewski et al , 2017; Natti et al , 2014).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Empirical validation of the framework will enable the generalisability of the research findings. Several future research opportunities exist: for example, as value is increasingly co-created in the ecosystem context, a B2B triadic or network context (Sales-Vivó et al, 2020) would provide a further basis to test the framework. The C-O-T-E framework has identified several factors; further research could explore and enhance these factors, and study the inter-relationship between them.…”
Section: Limitations and Future Research Directionmentioning
confidence: 99%